Proposed Recording System of Materials Usage in Say Cheese Restaurant (The Indonesian Journal of Business Administration, 2014)
Abstract - Say Cheese is a start up restaurant that struggling to survive in the very competitive restaurant business in Jatinangor. The problem facing the Say Cheese is the inaccuracy of recording the materials usage. Poor accuracy of materials usage record, requires more capital and make it difficult to conduct right pricing strategy. This study aims to find out what is causing inaccuracies in recording the materials usage on Say Cheese, and what the solution to resolve the recording inaccuracies. This study uses Inventory Record Accuracy (IRA) methods to measure the actual accuracy of materials usage records in Say Cheese. Then by ishikawa diagram, the root causes for these inaccuracies are defined. To resolve the the root causes, the solution are selected from solutions alternative using â€œDecision Matrixâ€. The results show the accuracy for recording the materials usage in Say Cheese is poor, mainly because the system for recording are still manual, relies heavily on the actions of people to do the recording. Making a computerized system, that can be automatically convert the sales data into materials usage data is the solution for the inaccuracy problem. The solution implemented into four phases. The phase are data and information gathering, material usage recording system making, standardization and regulation, and phase implementation dan evaluation phase. The implementation for the solution will be done in twelve weeks. Benefit that will be gain is the increase of recording accuracy.Â Keywords: culinary industry, inventory record accuracy, Ishikawa Diagram, Decission Matrix.